Legal Protection of Bhuju' Geger Religious Tourism in Bangkalan - Sumriyah, Sumriyah; Elmhemit, Hüseyin; Puspitasari, Firda; Nisa, Nabielatun; Jannah, Laila Nur (TRUNOJOYO LAW REVIEW, 2024)
Bhuju' Geger religious tourism in Bangkalan is an important spiritual destination often visited by the public but does not yet have adequate legal protection. In this context, legal protection for religious tourism areas is needed to ensure this tourism's sustainability, security, and management. This study aims to analyze the legal aspects that protect the Bhuju' Geger religious tourism area and identify challenges in implementing related laws. The contribution of this research is an effort to design a model of legal protection in the management of religious tourism or for tourists visiting religious tourism in Bangkalan Regency. The method used in this study is a normative approach, which analyzes relevant laws and regulations, literature studies, and interviews with related parties. The results of the study indicate that there is a legal vacuum and weaknesses in the implementation of regulations in force in the Bhuju' Geger religious tourism area. This study concludes that a more potent and specific legal policy is needed to protect this area, including strengthening regional regulations and active community participation in managing Bhuju' Geger religious tourism. The involvement of the community is integral to the success of these proposed changes.